Transaksi Via Internet: Mungkinkah Dibuat Standard Akuntansi? - Suryo Pratolo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2002)
We all know that Internet is so powerful in supporting globalization. One of the sector is in business transaction like e-commerce, e-shop, etc. Indeed, it makes easy for people to sell and buy some product in the world without barrier if they have money. Beside this positive effect, there are negative one. Computer crime threats this practice by thieving the money in credit card system. Of course it is so dangerous for people that have credit card facility. Because of that it is important not only to improving computer and internet safety but also improving accountability in the e-commerce or other e-bussiness practice by Good Accounting Standard.